Pregnancy rate, multiple pregnancy rate, and embryo quality: Clues for single blastocyst transfer from double blastocyst transfer in an unselected population - HARA, TETSUAKI (Reprod Med Biol, 2005)
Objective:  Minimizing multiple pregnancy is a priority in assisted reproduction. As implantation rates are critical to success and reduce multiple pregnancy, we investigated whether blastocyst grade determined implantation rate following double blastocyst transfer in unselected cases. Materials and Methods:  We studied 69 three‐cleavage stage embryo transfers and 64 two‐blastocyst transfers. Two blastocysts, or one when two blastocysts were not available, were transfered after evaluating the grade of blastocysts. The difference in pregnancy and implantation rates to patient age, the number of retrieved oocytes and grade of blastocysts were analyzed. Results:  Blastocyst and grade 3AA rates per fertilized egg were 50.3% and 26.0%, respectively. Following two‐blastocyst transfer, pregnancy rate per transfer, implantation rate per embryo, and multiple pregnancy rate per pregnancy were 39.1%, 26.5%, and 24.0%, respectively. Two‐blastocyst transfer achieved implantation more often than three‐cleavage‐stage embryo transfer, but did not reduce multiple pregnancy. Pregnancy, implantation, and multiple pregnancy rates did not reflect maternal age. Higher pregnancy and implantation rates per transfer were attained for with six or more oocytes retrieved or transfer of two‐blastocyst graded 3AA or higher especially when two or more blastocysts graded 3AA or higher are available, but the latter showed a high multiple pregnancy rate (38.5%). Conclusions:  Single embryo transfer could be carried out when two or more blastocysts of grade 3AA or higher have been developed. (Reprod Med Biol 2005; 4: 153–160)